Shaping and re-shaping the boundaries of working life - Foulkes Savinetti, Nicol; Riekhoff, Aart-Jan (Tampere, Finland : Tampere University Press, 2020)
This edited book brings together contributions by some of the top work-life researchers from Finland and abroad. It offers a series of short essay-type chapters covering a broad variety of topics related to how labour markets, work and working life are continuously changing. The book has a strong cross-national approach and stresses the importance of studying both microlevel changes within macrolevel contexts as well as the microlevel mechanisms of changes at the macrolevel. The chapters are grouped in four parts. Part I deals with how life courses have changed, with special focus on the entry of women to the labour market and the determinants of their economic contribution. Part II discusses two circuits of labour migration: that of mostly high-skilled and regulated work and that of mostly low-skilled and unregulated work. However, it also shows that the boundaries between those two are not always clear. Part III focuses on how work itself is changing, using the examples of women attorneys’ pro-bono work in Finland and Poland and the use of lean management in the Nordic public sector. Finally, in Part IV the authors explore the power of institutions and ideas in reshaping the way we work while labour markets are under pressure.
Vertaisarvioitu.
Julkaistu myös painettuna.
Kuvailun perustana verkkoaineisto; nimeke PDF-nimiösivulta (Trepo, katsottu 4.9.2023).
Keywords: työelämä; työmarkkinat; uudistukset; hyvinvointivaltio; sukupuoli; naiset; työmarkkina-asema; työvoiman liikkuvuus; työelämän suhteet; perustulo; suomalaiset; puolalaiset; siirtotyöläiset; kansainvälinen vertailu; arbetsliv; arbetsmarknaden; reformer; välfärdsstat; kön; kvinnor; ställning på arbetsmarknaden; arbetskraftens rörlighet; relationer i arbetslivet; basinkomst; finländare; polacker; gästarbetare; internationell jämförelse; Suomi; Puola; Pohjoismaat; Finland; Polen; Norden